2012
DOI: 10.1159/000342484
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous and Sequential Concurrent Myeloproliferative and Lymphoproliferative Neoplasms

Abstract: Concurrent manifestation of two chronic-stage myeloid and lymphoid/plasmacytoid neoplasms in one patient is rare and occurs in ≤1% of patients. There has been no systematic analysis of which combinations are frequent/infrequent and whether two concurrent diseases in one patient are clonally related or represent independent diseases. We therefore characterised a series of cases from our own archive (n = 65) and collected a large number of previously reported cases of patients in whom myeloid and lymphoid/plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 176 publications
1
16
0
1
Order By: Relevance
“…Earlier clinical studies have likewise demonstrated a beneficial effect in early stage B-CLL using nonpegylated interferon alpha 2a [3]. The diagnosis of concomitant CLL/MPN is a rare event and in a recent study analysis of prognostic markers for CLL demonstrated that in patients with a coexistent MPN, lymphoproliferative disorders follow a clinically indolent course [4,5].Our patient has achieved a substantial hematologic, molecular and splenic response in his PV after 22 months on low dose Pegasys. Moreover, he has achieved a favorable reduction in the B-cell CLL clonal population and a change in Zap-70 status from indeterminate to negative.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Earlier clinical studies have likewise demonstrated a beneficial effect in early stage B-CLL using nonpegylated interferon alpha 2a [3]. The diagnosis of concomitant CLL/MPN is a rare event and in a recent study analysis of prognostic markers for CLL demonstrated that in patients with a coexistent MPN, lymphoproliferative disorders follow a clinically indolent course [4,5].Our patient has achieved a substantial hematologic, molecular and splenic response in his PV after 22 months on low dose Pegasys. Moreover, he has achieved a favorable reduction in the B-cell CLL clonal population and a change in Zap-70 status from indeterminate to negative.…”
supporting
confidence: 52%
“…Earlier clinical studies have likewise demonstrated a beneficial effect in early stage B-CLL using nonpegylated interferon alpha 2a [3]. The diagnosis of concomitant CLL/MPN is a rare event and in a recent study analysis of prognostic markers for CLL demonstrated that in patients with a coexistent MPN, lymphoproliferative disorders follow a clinically indolent course [4,5].…”
mentioning
confidence: 99%
“…A recent study conducted on a total of 250 cases reported that the combination of a MPN with a B-CLL accounts for a 50% of the double-disease patients analyzed [72]. Moreover, in these cases the evaluation of JAK2V617F in different lineages is of increasing interest as it could help to understand if the myeloproliferative and lymphoproliferative disorders are both derived from the same pluripotent stem cell or just coincide.…”
Section: The Role Of Jak2 In Lymphomasmentioning
confidence: 99%
“…Only a few cases of concomitantly occurring MPN and LPN have been reported [3-8]. Laurenti et al published a multicenter retrospective study on the association of chronic lymphocytic leukemia (CLL) and concomitant MPN [9] but at present, no systematic analysis for MPN-LPN disease association is available and underlying pathogenic mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%